Occupational Exposure during Intraperitoneal Pressurized Aerosol Chemotherapy Using Doxorubicin in a Pig Model - Wongeon Jung; Mijin Park; Soo Jin Park; Eun Ji Lee; Hee Seung Kim; Sun Ho Chung; Chungsik Yoon (Elsevier, 2023)
Background: This study evaluated occupational exposure levels of doxorubicin in healthcare workers performing rotational intraperitoneal pressurized aerosol chemotherapy (PIPAC) procedures. Methods: All samples were collected during PIPAC procedures applying doxorubicin to an experimental animal model (pigs). All procedures were applied to seven pigs, each for approximately 44 min. Surface samples (n = 51) were obtained from substances contaminating the PIPAC devices, surrounding objects, and protective equipment. Airborne samples were also collected around the operating table (n = 39). All samples were analyzed using ultra-high performance liquid chromatography-mass spectrometry. Results: Among the surface samples, doxorubicin was detected in only five samples (9.8%) that were directly exposed to antineoplastic drug aerosols in the abdominal cavity originating from PIPAC devices. The telescopes showed concentrations of 0.48-5.44 ng/cm2 and the trocar showed 0.98 ng/cm2 in the region where the spraying nozzles were inserted. The syringe line connector showed a maximum concentration of 181.07 ng/cm2, following a leakage. Contamination was not detected on the surgeons' gloves or shoes. Objects surrounding the operating table, including tables, operating lights, entrance doors, and trocar holders, were found to be uncontaminated. All air samples collected at locations where healthcare workers performed procedures were found to be uncontaminated. Conclusions: Most air and surface samples were uncontaminated or showed very low doxorubicin concentrations during PIPAC procedures. However, there remains a potential for leakage, in which case dermal exposure may occur. Safety protocols related to leakage accidents, selection of appropriate protective equipment, and the use of disposable devices are necessary to prevent occupational exposure.